MAIT cells altered phenotype and cytotoxicity in lupus patients are linked to renal disease severity and outcome - Litvinova, Elena; Bounaix, Carine; Hanouna, Guillaume; Da Silva, Jennifer; Noailles, Laura; Beaudoin, Lucie; Padden, Michael; Bellamri, Nessrine; Lehuen, Agnès; Daugas, Eric; Monteiro, Renato C.; Flament, Héloïse (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease in which circulating immune complexes can cause different types of glomerulonephritis, according to immune deposits and to the type of glomerular cell injury. Proliferative lesions represent the most severe form of lupus nephritis (LN) and often lead to kidney failure and death. Mucosal-associated invariant T (MAIT) cells are a subset of innate-like T cells that recognize microbial-derived ligands from the riboflavin synthesis pathway. Although abundant in peripheral blood, MAIT cells are enriched in mucosal and inflamed tissues. While previous studies have reported concordant results concerning lower MAIT cell frequencies in the blood of SLE patients, no information is known about MAIT cell function and LN severity. In the current study, we analyzed the baseline phenotype and function of peripheral blood MAIT cells by flow cytometry in 26 patients with LN and in a control group of 16 healthy individuals. We observe that MAIT cell frequencies are markedly reduced in blood of LN patients. MAIT cells from patients have an altered phenotype in terms of migration, proliferation and differentiation markers, notably in most severe forms of LN. Frequencies of PMA/ionomycin stimulated MAIT cells secreting effector molecules, such as pro-inflammatory IL-17 and cytotoxic protein granzyme B, are higher in LN patients. Patients undergoing a complete renal remission after immunosuppressive therapy had higher MAIT cell frequency, lower expression of proliferation marker Ki-67 and granzyme B (GzB) at inclusion. Remarkably, GzB production defines a predictive model for complete remission.In conclusion, we report here that blood MAIT cells display proinflammatory and cytotoxic function in severe lupus nephritis which may play a pathogenesis role, but without association with systemic lupus activity. Finally, low cytotoxic profile of MAIT cells may represent a promising prognostic factor of lupus nephritis remission one year after induction therapy.